STUDY OF A QUASI-RESONANT CONVERTER WITH SYMMETRICAL COMPONENTS - Nagy, István (Periodica Polytechnica Mechanical Engineering, 1990)
A symmetrical DC-DC thyristor converter supplied by asymmetrical input voItages is investigated with symmetrical components. The converter needs no forced commutation and operates at high frequency at fuII load. The operational states of the so-called symmetrical, asymmetrical and general energy supply are discussed. The converter can be operated as an active filter. An approximate description of the transient response is given.